Control de Calidad de Datos Oceanográficos Mediante una Herramienta Computacional - Salcedo Parra, Octavio José; Puente, Francisco Javier; Ortiz, Ruby Viviana (Ingeniería, 2007)
This paper describes an application of Information Technologies (IT) in the data-processing and implementation of quality tests to oceanographic data measured by a wave directional ocean buoy with the goal of having reliable information for forecasting in the field of oceanography. The development of computational algorithms and the allocation of qualification flags are integrated into the development of a computational tool built under the Rational Unified Process which, according to the standards of the program International Exchange and Ocean Information (IODE - COI),validate the data measured by this kind devices: Waverider (wave) and embedded thermistor (temperature), and ADCP (current), and the allocation of quality flags from rules and algorithm developedfrom research and consulting enhancements documents of the area that meet the recommendations and experiences of the international oceanographic community in this area. As a result of this research was a software tool called -Y´ZuNaMy¡ which ensures that data measured by this kind of sensors that investors are currently at anchor of the Colombian coast, are subjected to every step that includes oceanographic data control quality (including verification of their qualifications and consistency), in this context will ensure interoperability under the format NetCDF (Network Common Data Form) widely used and accepted by the international community to exchange oceanographic measurements.